METHODOLOGICAL PRINCIPLES OF THE FORMATION OF THE PARADIGM FOR THE SALE - NEKHAI, Victoriia; KOLOKOLCHYKOVA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In order to achieve the epistemological result, the concept of "sales", "sales organization" was considered, the interpretation of these concepts by scientists was given, and the real circumstances of the sale of enterprise products were analyzed. The purpose of the article is to generalize the methodological foundations of the formation of the paradigm of sales of enterprise products. To achieve the goal, general scientific and specific methods were used, in particular, the method of logical generalization, scientific abstraction, comparison, empirical, graphic... The conceptual apparatus "sales" was studied by comparing it with other types of activity, namely, it was defined as an economic category based on the statement that sales activity has its own individual characteristics and is clearly defined as one of the influential functional links of the enterprise’s economic activity. This will make it possible to clearly define the features, tasks and the level of influence of sales on the level of development of the enterprise. As a result of the conducted empirical research and logical generalization, regularities and principles of sales activity were revealed, and new scientific knowledge regarding the sales paradigm was formed. The scientific novelty of the obtained results lies in the improvement of the methodological foundations of the formation of the sales paradigm, which approves it as an economic category, which is a sequence of measures for the sale of the company’s products based on the use of marketing methods and its organizational adequacy to ensure the satisfaction of demand and the achievement of the company’s profit. The given categorical model substantiates the ratio of the "sales" and "marketing" categories. The subject of further consideration is the study of methods of organization and management of enterprises by industry orientation, approaches to the development of the latest methods of sales organization based on the introduction of consolidated marketing.